Treatment Outcome in Pediatric Acute Lymphoblastic Leukemia With Hyperleukocytosis in the Yeungnam Region of Korea: A Multicenter Retrospective Study. Issue 4 (3rd May 2020) - Park, Kyung Mi; Yang, Eu Jeen; Lee, Jae Min; Hah, Jeong Ok; Park, Sang Kyu; Park, Eun Sil; Lim, Jae Young; Kim, Ji Yoon; Park, Jikyoung; Shim, Ye Jee; Kong, Seom Gim; Lim, Young Tak
Abstract : Acute lymphoblastic leukemia (ALL) with hyperleukocytosis at diagnosis is associated with early morbidity and mortality due to complications of leukostasis. Of 535 pediatric ALL patients (January 2004 to December 2016 from the Yeungnam region of Korea), 72 (13.5%) patients with an initial white blood cell (WBC) count of ≥100×10 9 /L were included in this study, of whom 38 patients had extreme hyperleukocytosis (WBC>200×10 9 /L) at diagnosis. Fourteen patients (19.4%) had ≥1 early respiratory and neurologic complications during induction therapy. Relapse occurred in 8 patients (24.2%) with extreme hyperleukocytosis and in 1 patient (3.0%) with an initial WBC count of 100 to 200×10 9 /L ( P =0.012). Estimated 10-year event-free survival rate (EFS) and overall survival rate were 78.3%±8.4% and 82.6%±7.7%, respectively. The 10-year EFS was significantly lower in patients with an initial WBC count of >200×10 9 /L than in those with an initial WBC count of 100 to 200×10 9 /L (65.7%±13.4% vs. 91.2%±7.9%; P =0.011). The 10-year EFS and overall survival rate did not differ significantly between patients with extreme hyperleukocytosis who received hematopoietic stem cell transplantation and those who received chemotherapy. In conclusion, pediatric ALL with hyperleukocytosis can lead to early complications and mortality. Patients with initial extreme hyperleukocytosis showed significantly poorer prognosis than those with WBC counts of 100 to 200×10 9 /L.